STEAM GASIFICATION OF SOME MONGOLIAN COALS - B, Tungalagtamir; E, Enkhtsetseg; Lumen, Chao; M, Narantsetseg; B, Avid; B, Ulziibat (Proceedings of the Mongolian Academy of Sciences, 2017)
The gasification tests for the Alagtolgoi and Ailbayan coal deposits were conducted in the temperature up to 850°C using bench scale reactor in order to evaluate product gas composition. Prior to the gasification experiments, the raw coal was pyrolysed in a stainless steel reactor under N2 atmosphere at a temperature of 500°C for 1 h. General behavior of the coal conversion was quite similar for both coals. The gasification tests show that an increase in temperature enhances the formation of hydrogen, carbon dioxide and carbon monoxide. The highest yield of hydrogen and carbon dioxide concentrations of the Ailbayan coal are achieved at temperature of 850°C, which were 2.859 mmol⋅g-1⋅min-1 and 1.054 mmol⋅g-1⋅min-1 respectively. However maximum rate of hydrogen for Alagtolgoi subbituminous coal reached around 800°C. Overall results show that the maximum gasification rate is reached earlier for subbituminous coal than for bituminous coal, but product gas evolution was higher for the investigated bituminous coal.